Fine Structure in Electronic Spectra of Cyanine Dyes: Are Sub‐Bands Largely Determined by a Dominant Vibration or a Collection of Singly Excited Vibrations?. Issue 9 (23rd February 2018) - Mustroph, Heinz; Towns, Andrew
Abstract: This work critically examines attempts to model the fine structure apparent in electronic spectra of cyanine dyes and their analogues. Numerous computational studies reported over the past decade attribute the origin of sub‐bands and their relative intensities to vibronic transitions in which the relevant electronic transition is coupled, irrespective of symmetry, with a collection of vibrations. It is contended that this type of approach is not supported by experimental evidence. An argument is reiterated for a more appropriate model that adheres closely to fundamental principles and fits the data. It stipulates that essentially just one symmetric vibration, carbon–carbon bond stretching of the cyanine polymethine chain, dominates the coupling and is responsible for the observed fine structure. Furthermore, it is pointed out that the intensities of the sub‐bands are readily explained by means of the Franck–Condon principle. Abstract : Which vibration? Sub‐bands in electronic spectra of cyanine dyes are readily explained as vibronic transitions by means of the Franck–Condon principle and essentially just one symmetric carbon–carbon bond stretching vibration of the cyanine polymethine chain. Contrary numerous computational studies reported over the past decade attribute the origin of sub‐bands and their relative intensities to a collection of vibrations that couple the electronic transition. This work critically examines attempts to model the fine structure apparent in electronic spectra of cyanine dyes.